2010
DOI: 10.1080/14786410802696429
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal natural products from the aerial parts ofRubus niveus

Abstract: Studies on the aerial parts of Rubus niveus yielded six known compounds, 3,5-dihydroxy benzoic acid C(7)H(6)O(4), (1), gallic acid C(7)H(6)O(5) (2), ethyl galactoside (3), oleanolic acid (4), beta-sitosterol (5) and 3-O-[beta-D-galactopyranosyl-(12)-D-glucopyranoside (6). Besides this, a gallic acid derivative with methyl substitution was synthesised as tetramethyl gallate (3). Together with this derivative, compounds 1, 2, the alcohol soluble, chloroform soluble and petroleum ether soluble extracts of the aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Also, the mortality of M. incognita J2 was 100% after 12 h incubation with 1.0 mg/ml of gallic acid purified from TNB [52]. According to Sultana et al [53], 3,5-DHBA purified from the aerial parts of Rubus niveus show strong nematicidal activity against M. incognita, exhibiting 100% mortality of M. incognita after 48 h at 5 mg/ml. In this study, nematicidal activity was also determined for the 3,4-DHBA purified from TNB.…”
Section: Discussionmentioning
confidence: 98%
“…Also, the mortality of M. incognita J2 was 100% after 12 h incubation with 1.0 mg/ml of gallic acid purified from TNB [52]. According to Sultana et al [53], 3,5-DHBA purified from the aerial parts of Rubus niveus show strong nematicidal activity against M. incognita, exhibiting 100% mortality of M. incognita after 48 h at 5 mg/ml. In this study, nematicidal activity was also determined for the 3,4-DHBA purified from TNB.…”
Section: Discussionmentioning
confidence: 98%
“…Several reports have described that the secretion of extracellular proteinases plays an important role in the nematicidal activity of antagonistic strains of Bacillus , Pseudomonas , and Stenotrophomonas (911). We also found that the genome contains gene loci for resorcinol, terpene, arylpolyene, siderophore, and thiazole/oxazole-modified microcin (TOMM) identified by antiSMASH analysis (12); various resorcinol compounds and plantazolicin (a member of the TOMM family) have been known to be involved in nematicidal activity (1315). Overall, the whole-genome analysis of D. acidovorans strain HK171 provides a genetic foundation for the understanding of biocontrol mechanism to root-knot nematode.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Two phenolic acids, 3,5-dihydroxybenzoic acid (134) and gallic acid (141), were isolated from the aerial parts of Rubus niveus (Rosaceae) with their nematicidal activity against freshly hatched secondary stage juveniles of M. incognita [107]. Another two nematicial phenolic compounds namely vanillic acid (or called 3-methoxy-4-hydroxy benzoic acid, 140) and methyl benzoate (142) against nematode M. incognita were isolated from the aerial parts of Buddleja crispa (Loganiaceae) [108].…”
Section: Phenols and Phenolic Acidsmentioning
confidence: 99%